Topics in fluvial and lagoon morphodynamics - Solari, Luca (Strumenti per la didattica e la ricerca, 2002)
The present book covers topics both on fluvial and lagoon morphodynamics. The first part is dedicated to tidal environments. Topics include an overview of main morphological features and mechanisms of estuaries and tidal channels and a model devoted to investigate flow field pattern and bed topography in tidal meandering channels and a comparison with recent observational evidence of meanders within different tidal environments. The general failure of Bagnold hypothesis when applied to equilibrium bedload transport at even relatively modest transverse slope is demonstrated. A new model is then proposed based on an empirical entrainment formulation of bed grains.